2021
DOI: 10.1088/1742-6596/1957/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interactive online learning by Pear Deck during COVID-19 pandemic era

Abstract: The COVID-19 pandemic surprises the world, switches every learning activity to online learning and increases online education platforms’ demand. However, teachers must be careful in choosing online education platforms as some online learning applications may look exciting but not give meaningful learning for students. This study uses the Pear Deck to build meaningful learning by establishing the interaction in a mindful activity. As an add-on application of PowerPoint or Google slides, Pear Deck is one solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
2
8
0
1
Order By: Relevance
“…e findings of our research are also supported by the findings in reference [2], which state that students found that Pear Deck engaged them to be more participative in this criterion, as Pear Deck changed students' passive behavior to be active social learners.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…e findings of our research are also supported by the findings in reference [2], which state that students found that Pear Deck engaged them to be more participative in this criterion, as Pear Deck changed students' passive behavior to be active social learners.…”
Section: Discussionsupporting
confidence: 87%
“…Pear Deck allows students to become self-motivated and active learners by allowing them to ask inquiring and intuition-challenging questions, instead of simply relaying facts [22]. Also, as stated in the study of reference [2], "the use of Pear Deck supports teachers in building engaging activities and allowing students to be active and time-on-task performers. In addition, Pear Deck also allows students to enhance their comprehension by reflecting on the teacher's feedback."…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…and Quizizz include prepared quizzes ( 42 , 56 ). PearDeck is an ARS add-on to Google Slides that allows an instructor to host quizzes and interactive slides while saving the student responses for a record of the formative assessment ( 57 61 ). While questions administered by the previous ARSs required respondents to reply individually, Baamboozle is a web-based ARS but is more like gamified notecards, with only the instructor responding on behalf of student teams ( 34 ).…”
Section: Digital Tools To Increase Engagement In Ia Sessionsmentioning
confidence: 99%
“…Five prior related studies were conducted in this archipelago dealing with the use of online formative assessment. The first study was run by Fitriana and Purnamasari (2021) Haryani and Ayuningtyas (2021) strongly prompted Indonesian EFL teachers to integrate Pear Deck online learning application as one of the formative assessment types since the majority of learners were capable of expanding their target language knowledge, magnifying their learning endeavor, and elevating their higher-order thinking skills. In the third study, Lutfiana and Suwartono (2020) highly advocated that Indonesian EFL teachers to ascertain the reliability, credibility, and authenticity of the online formative assessment incorporating in their learning processes to enable all learners to improve their target language competencies to the utmost potential.…”
Section: Introductionmentioning
confidence: 99%